EFFECTIVENESS OF COOPERATIVE LEARNING MODEL OF KANCING GEMERINCING TECHNIQUES ON MATHEMATICAL LEARNING OUTCOMES - Lusiana Pratiwi; Suparman Suparman (Universitas Ahmad Dahlan, 2018)
The researcher does this research because the result of the learning mathematics is still low. This research aims to find out the learning mathematics results by using the kancing gemerincing technique of the cooperative learning model on second-semester student grade VIII in SMP Negeri 4 Yogyakarta at Academic Year 2016/2017. The research population is all of the second-semester students grade VIII of SMP Negeri 4 Yogyakarta academic year 2016/2017, which consists of 5 classes: VIII A, VIII B, VIII C, VIII D, and VIII E with the number of 168 students. The sampling technique uses random sampling, where class VIII D as the experimental class I and class VIII B as the experimental class II. The data collecting techniques use documentation, interview, and test method. The testing instruments use validity tests, discriminating power tests, and reliability tests. The data analysis technique used for the prerequisite test uses the normality test with the chi-square and homogeneity test by Bartlet test formula. Moreover, the t-test is used for the hypothesis test. The result of the research shows at the 5% significance level and dk= 66 that (1) there are differences in mathematic learning result among the students who use the kancing gemerincing technique of cooperative learning model and who uses the TS-TS technique of cooperative learning model on second-semester students grade VIII of SMP Negeri 4 Yogyakarta in academic year 2016/2017. It is indicated by the result of tcount = 2,4339 and ttable = 1,9983, so tcount > ttable. (2) The kancing gemerincing technique of cooperative learning model is more effective than the TS-TS technique of cooperative learning model toward the mathematic learning result of the second-semester students grade VIII in SMP Negeri 4 Yogyakarta at academic year 2016/2017. It is showed by the result of tcount =2,4339 and ttable =1,6693, so tcount > tcount.